Epimenides' midday sleep - G. de Campos, Rogério (Revista Archai, 2023)
From the scene of the singing cicadas in the Phaedrus, we will show the affinities between the mention of the dangerous sleep at noon (Phdr. 258e6-259d8) and a mythical episode in the life of Epimenides. Next, we will look at the possible affinities between the description of Dionysian madness (Phdr. 244d5-245a1) and the type of divination practiced by Epimenides of Crete (DK 3 B 1-25). From these approaches, we intend to describe and elucidate the common imaginary with which Plato elaborates his reception and assimilation of the archaic poetic tradition in his philosophy.